ADRA2B deletion variant and enhanced cognitive processing of emotional information: A meta-analytical review. (September 2018) - Xie, Weizhen; Cappiello, Marcus; Meng, Ming; Rosenthal, Robert; Zhang, Weiwei
Highlights: ADRA2B deletion variant can facilitate cognitive processing of emotional information. This genetic effect does not manifest in task performance when non-emotional content is used. These observations can be generalized across studies and laboratories. These effects can also be moderated by some study-level factors, such as targeted cognitive processes and task procedures. Abstract: This meta-analytical review examines whether a deletion variant in ADRA2B, a gene that encodes α2B adrenoceptor in the regulation of norepinephrine availability, influences cognitive processing of emotional information in human observers. Using a multilevel modeling approach, this meta-analysis of 16 published studies with a total of 2752 participants showed that ADRA2B deletion variant was significantly associated with enhanced perceptual and cognitive task performance for emotional stimuli. In contrast, this genetic effect did not manifest in overall task performance when non-emotional content was used. Furthermore, various study-level factors, such as targeted cognitive processes (memory vs. attention/perception) and task procedures (recall vs. recognition), could moderate the size of this genetic effect. Overall, with increased statistical power and standardized analytical procedures, this meta-analysis has established the contributions of ADRA2B to the interactions between emotion and cognition, adding to the growing literature on individual differences in attention, perception, and memory for emotional information in the general population.